Regulation of transcription termination by glucosylated hydroxymethyluracil, base J, in Leishmania major and Trypanosoma brucei - Reynolds, David (Oxford University Press, 2014)
Base J, β-d-glucosyl-hydroxymethyluracil, is an epigenetic modification of thymine in the nuclear DNA of flagellated protozoa of the order Kinetoplastida. J is enriched at sites involved in RNA polymerase (RNAP) II initiation and termination. Reduction of J in Leishmania tarentolae via growth in BrdU resulted in cell death and indicated a role of J in the regulation of RNAP II termination. To further explore J function in RNAP II termination among kinetoplastids and avoid indirect effects associated with BrdU toxicity and genetic deletions, we inhibited J synthesis in Leishmania major and Trypanosoma brucei using DMOG. Reduction of J in L. major resulted in genome-wide defects in transcription termination at the end of polycistronic gene clusters and the generation of antisense RNAs, without cell death. In contrast, loss of J in T. brucei did not lead to genome-wide termination defects; however, the loss of J at specific sites within polycistronic gene clusters led to altered transcription termination and increased expression of downstream genes. Thus, J regulation of RNAP II transcription termination genome-wide is restricted to Leishmania spp., while in T. brucei it regulates termination and gene expression at specific sites within polycistronic gene clusters.